The first few cases and fatalities of Corona Virus Disease 2019 (COVID-19) in the Eastern Mediterranean Region of the World Health Organization: A rapid review - Muna Abed Alah (14779534) (2020)
In December 2019, a cluster of atypical Pneumonia cases in Wuhan, China were reported to the World Health Organization (WHO). Later, those cases were attributed to a novel respiratory virus currently known as COVID-19. The infection is affecting every continent. It was characterized by WHO as a global pandemic on 11 March 2020. Countries worldwide are implementing various preventive measures to contain the spread of the infection such as travel and trade restrictions, closure of educational institutions and shops, and some took more strict measures such as imposing curfew. WHO is emphasizing the importance of early detection of cases, contact tracing, risk communications, implementing multisectoral approach in order to combat COVID-19 infection. Countries should provide the public with accurate, transparent information about the local and global situation of this escalating infection. Much uncertainty still surrounds this viral infection, its modes of transmission and dynamics. Epidemiological investigations particularly for the first few cases of COVID-19 infection are critical to expand our knowledge about this evolving pandemic. In this review we summarized the data available about the first few cases and fatalities of COVID-19 infection up to 18 March 2020 across Eastern Mediterranean Region of the World Health Organization. such data were only available in websites of ministries of health of the targeted countries, WHO situational reports, online newspapers, and other media channels and this gave us an idea about the amount and type of data available for the public regarding this evolving infection. Other Information Published in: Journal of Infection and Public Health License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jiph.2020.06.009